2015
DOI: 10.1128/aem.03032-14
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Surveillance Study of Clostridium difficile in Australian Neonatal Pigs Shows High Prevalence and Heterogeneity of PCR Ribotypes

Abstract: Clostridium difficile is an important enteric pathogen of humans and the cause of diarrhea and enteritis in neonatal pigs. Outside Australia, prevalence in piglets can be up to 73%, with a single PCR ribotype (RT), 078, predominating. We investigated the prevalence and genotype of C. difficile in Australian pig herds. Rectal swabs (n ‫؍‬ 229) were collected from piglets aged <7 days from 21 farms across Australia. Selective culture for C. difficile was performed and isolates characterized by PCR for toxin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 35 publications
3
73
4
1
Order By: Relevance
“…While there is no conclusive evidence that contaminated food leads to CDI in humans, studies have found that retail vegetables are contaminated with C. difficile strains similar to those affecting humans (31,32). Likewise, the C. difficile ribotypes frequently isolated in the current study, such as 014/020 and 056, are common ribotypes found in piglets and veal calves, respectively, in Australia (33,34). Therefore, the possibility of food being a vehicle of C. difficile transmission cannot be ruled out.…”
Section: Discussionmentioning
confidence: 81%
“…While there is no conclusive evidence that contaminated food leads to CDI in humans, studies have found that retail vegetables are contaminated with C. difficile strains similar to those affecting humans (31,32). Likewise, the C. difficile ribotypes frequently isolated in the current study, such as 014/020 and 056, are common ribotypes found in piglets and veal calves, respectively, in Australia (33,34). Therefore, the possibility of food being a vehicle of C. difficile transmission cannot be ruled out.…”
Section: Discussionmentioning
confidence: 81%
“…Potential sources of CDI in Australian food production animals C. difficile is commonly found in Australian piglets, with 67% period prevalence in a study of neonatal herds 29 . These rates are higher than that reported in major pork-producing countries [30][31][32] .…”
Section: Under the Microscopementioning
confidence: 99%
“…2 However, meticulous adherence to these interventions is unlikely to remove the risk of CDI entirely due the widespread presence of C. difficile in healthcare settings, the environment, livestock and (occasionally) food. [3][4][5] Therefore, there is an urgent need for effective CDI prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%